Arterial Stiffness and Gait Speed in Older Adults with and without Peripheral Arterial Disease - Watson, NL (2010)
BACKGROUND: Central arterial stiffness is increasingly recognized as an important predictor of cardiovascular events and mortality in older adults; however, few studies have evaluated the association of arterial stiffness with mobility decline, a common consequence of vascular disease. METHODS: We analyzed the association of pulse wave velocity (PWV), a measure of aortic stiffness, with longitudinal gait speed over seven years in 2,172 participants in the Health, Aging and Body Composition (Health ABC) Study (mean age ± SD 73.6 ± 2.9 years, 48% men, 39% black). RESULTS: In mixed-effects models adjusted for demographics, each SD (396 cm/s) higher PWV was associated with 0.015 (SE 0.004) m/s slower gait at baseline and throughout the study period in the full cohort (p < 0.001); this relationship was largely explained by hypertension and other vascular risk factors. Among participants with peripheral arterial disease (PAD) (n = 261; 12.7%) each SD higher PWV was independently associated with 0.028 (SE 0.010) m/s slower gait speed at baseline and throughout the study period (p < 0.01). CONCLUSIONS: These findings suggest that aortic stiffness may be especially detrimental to mobility in older adults with already compromised arterial function.